Where Is the Carbon Tax after Thirty Years of Research? - Timilsina, Govinda R. (World Bank, Washington, DC, 2018)
This paper takes a dive into the deep literature on the carbon tax accumulated through active and continuous research over the past 30 years. It also presents the ongoing debate and implementation of the carbon tax in practice. The paper discusses the evolution of the carbon tax literature, classifying it by the issues investigated and methodology used for the investigation. It finds that the literature enlightens four key issues: (i) economic impacts, (ii) choices for revenue recycling, (iii) distributional implications, and (iv) competitiveness and border tax adjustment. Quantitative analysis, especially computable general equilibrium modeling, is the main method employed in the literature. The study shows that potential adverse economic impacts and competitiveness concerns are the main impediments to the introduction of the carbon tax. Extensive examinations of carbon tax issues at the global, regional, and country levels have led to innovative measures to address these concerns. While the carbon tax was mainly a subject of academic discussion until few years back, it has generated good attention for policy makers, particularly after the Paris Agreement on climate change, and is being considered as one of the main market instruments to address global climate change. Although several important issues related to the carbon tax have been well researched, its potential interactions with poverty and shared prosperity are yet to be investigated.